2. Work in Progress: Border Conflicts and Tools for Stabilization. From Ancient Greece to Contemporary Europe: FeBo Project Report 2024, 1 - Elena Franchi (Teiresias Journal Online, 2024)
Elena FRANCHI (Università di Trento) Border Conflicts and Tools for Stabilization. From Ancient Greece to Contemporary Europe FeBo Project Report 2024, 1